Whistler Wave Generation by Anisotropic Tail Electrons During Asymmetric Magnetic Reconnection in Space and Laboratory - Jongsoo Yoo; J. Jara‐Almonte; Evan Yerger; Shan Wang; Tony Qian; Ari Le; Hantao Ji; Masaaki Yamada; William Fox; Eun‐Hwa Kim; Li‐Jen Chen; Daniel J. Gershman (Geophysical Research Letters)
Abstract Whistler wave generation near the magnetospheric separatrix during reconnection at the dayside magnetopause is studied with data from the Magnetospheric Multiscale mission. The dispersion relation of the whistler mode is measured for the first time near the reconnection region in space, which shows that whistler waves propagate nearly parallel to the magnetic field line. A linear analysis indicates that the whistler waves are generated by temperature anisotropy in the electron tail population. This is caused by loss of electrons with a high velocity parallel to the magnetic field to the exhaust region. There is a positive correlation between activities of whistler waves and the lower hybrid drift instability both in laboratory and space, indicating the enhanced transport by lower hybrid drift instability may be responsible for the loss of electrons with a high parallel velocity.